THE EFFECTIVENESS OF DIGITAL AND PRINTED COMICS TO TEACH MONOLOGUE OF VISUAL AND AUDITORY STUDENTS A case of the Tenth Year Students of State Senior High School 1 Ungaran - Setyorini, Wahyu; Hartono, Rudi (English Education Journal, 2017)
This study attempts to know the effectiveness of digital comics to teach monologue of visual and auditory students. This study used quantitative approach and experimental study as its research design. The subjects of this study were the students of grade X of State Senior High School 1 Ungaran. To collect the data, the researcher used test, questionnaire, and documentation.  The result of the study shows that digital comics is effective to teach monologue of visual students. Printed comics is effective to teach monologue of visual students. Digital comics is effective to teach monologue of auditory students. Printed comics is effective to teach  monologue of auditory students. Digital comics is not more effective than printed comics to teach  monologue of visual students. Digital comics is more effective than printed comics to teach speaking monologue of auditory students. And the last, there is interaction among the teaching media, students learning styles, and studentsâ speaking. Therefore, digital comics is effective to teach monologue of visual and auditory students.